Promoting or inhibiting? The impact of urban–rural integration on the green transformation of arable land utilization: Evidence from China’s major grain-producing regions - Wanmin Zhao; Yijia Gao; Mengna Tang; Aihui Ma (Ecological Indicators)
Exploring how urban–rural integration influences the green transformation of arable land utilization is crucial for resolving the conflict between “protecting arable land” and “promoting development” and achieving high-quality agricultural and rural development. This study focuses on 170 prefecture-level cities in China’s major grain-producing regions. Based on green development goals and symbiosis theory, the three-dimensional kernel density and Moran’s I are employed to analyze the temporal and spatial evolution and spatial agglomeration characteristics of the green transformation of arable land utilization and urban–rural integration. Based on the theory of factor induced substitution, we applied panel regression and mediation models to analyze the impacts, heterogeneity, and mechanisms of urban–rural integration on the green transformation. The findings indicate that: (1) From 2013 to 2022, green transformation and urban–rural integration in the study area improved, showing clear temporal and spatial differentiation. (2) The green transformation exhibited a moderate agglomeration trend of “rising, then falling, and recovering,” while urban–rural integration’s collaborative pattern strengthened, though the level remained low. (3) Urban–rural integration directly promoted the initial green transformation, but inhibited high-level transformation. It drove the green transformation through mediating effects like demand-driven, infrastructure development, and digitalization. Urban–rural integration had significant promoting effects on spatial and functional transformations, but a weaker impact on model transformation. Regional heterogeneity was also observed. Therefore, it is essential to adopt context-specific, coordinated development to overcome geographic and industrial constraints, activate spatial and functional transformation, overcome the bottleneck of model transformation, strengthen digital infrastructure support, and improve the urban–rural integration mechanism.